Effect of Raw Material Supply Optimization of Engineering And Production Of Products So Gondorukem And Turpentine (Case Study on Gondorukem and Turpentine Factory on Perhutanioffice West Java Regional Division) - Suryatini, Dwi; Indupurnahayu, Indupurnahayu; Ishardyatmo, Handono (Jurnal Manajemen, 2015)
The results showed that : 1 ) The regression coefficient was significant to the outcome of t -1.509 < t table 1.671 and 0.137 significance level > 0.05 means the raw materials policy regression equation (X1) of the finished product Gum Rosin and Turpentine (Y) declared not significant, 2) Value of the coefficient for the variable engine optimization (X2) to the value of b2 = 0.878 in the multiple linear regression equation Y = a + b1X1 + b2 = 0.878 b2X2 so that means every increase of 1 point of the optimization of the engine it will affect the finished product gondorukem and turpentine on Perhutanioffice West Java Regional Division by 0.878 points and the other independent variables constant, 3) Material relationship with the optimization engine in Java Regional Division Perhutanioffice Baratmenunjukan kelinearan a very strong relationship between raw materials (X1) with engine optimization (X2), 4) Raw materials and optimization engine gondorukem effect on the finished product and turpentine. Percentage of raw material variables influence the optimization engine and machine jointly obtained value of R Square of 1.000 or (100 %). This shows that the percentage contribution of independent variables , namely raw materials and the optimization of the engine together against Gum Rosin and Turpentine finished product at 100%.